Temporal evolution of wetting transitions of graphene oxide coated on roughened polyvinyl chloride surfaces. (December 2020) - Song, Zhixiong; Lin, Eric Shen; Uddin, Md. Hemayet; Ong, Jian Wern; Abid, Hassan Ali; Xiong, Zhiyuan; Li, Dan; Liew, Oi Wah; Ng, Tuck Wah
Graphical abstract: Highlights: GO on roughened PVC surfaces show contact angles that change from 16° to zero within 3 s. When dispensed 180 min after surface preparation the contact angle changed from 32° to 4° in 35 s. These temporal wetting transitions are not observed with GO deposited on glass or on unroughened PVC surfaces. Wetting is promoted by GO solution filling into asperities from roughening based on mechanistic model advanced. The GO solution filling is lessened with the onset of evaporation, causing a reduction in substrate wetting. Abstract: In this work, the deposition of graphene oxide (GO) on roughened polyvinyl chloride (PVC) surfaces revealed contact angle changes from 16° to zero within 3 s when a 50 μL water drop was dispensed on them. When the water drop was dispensed 180 min after the surface was prepared, the contact angle changed from 32° to 4° after 35 s. Such time-dependent wetting transition was however not observed with GO deposited on glass nor on unroughened PVC surfaces. A mechanistic explanation for the observed temporal evolution of wetting properties was provided. Optical profilometry scans conducted provided insights on the effect of surface roughness on GO deposition characteristics after evaporation of the GO solution off the substrate surface. The substrate roughness and evaporation dependent temporal wetting transitions of graphene oxide (GO) coating found here is essential in various sensing, transporting, harvesting and actuating applications.